2021
DOI: 10.1002/adma.202108360
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Nanomicelles for the Topical Delivery of Aflibercept to Treat Retinal Neovascular Disease

Abstract: The traditional intravitreal injection delivery of antivascular endothelial growth factor (anti‐VEGF) to the posterior segment of the eye for treatment of retinal diseases is invasive and associated with sight‐threatening complications. To avoid such complications, there has been significant interest in developing polymers for topical drug delivery to the retina. This study reports a nanomicelle drug delivery system made of a copolymer EPC (nEPCs), which is capable of delivering aflibercept to the posterior se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 52 publications
0
32
0
Order By: Relevance
“…Taking into consideration the viscosity of hydrogels, which may cause ocular discomfort, and blurring of vision, we explored the use of EPC as nanomicelles for topical delivery of anti-VEGF (Aflibercept). 102 This is the first time the intrinsic anti-angiogenic effects of nEPC was reported (Figure 5A). More importantly, the nEPC could achieve a therapeutic Aflibercept concentration in murine vitreous due to its significantly high encapsulation efficiency and ability to deliver the protein across the corneal epithelial and sclera barriers.…”
Section: Thermogels For Posterior Eye Segment Proliferative Vascular ...mentioning
confidence: 68%
See 1 more Smart Citation
“…Taking into consideration the viscosity of hydrogels, which may cause ocular discomfort, and blurring of vision, we explored the use of EPC as nanomicelles for topical delivery of anti-VEGF (Aflibercept). 102 This is the first time the intrinsic anti-angiogenic effects of nEPC was reported (Figure 5A). More importantly, the nEPC could achieve a therapeutic Aflibercept concentration in murine vitreous due to its significantly high encapsulation efficiency and ability to deliver the protein across the corneal epithelial and sclera barriers.…”
Section: Thermogels For Posterior Eye Segment Proliferative Vascular ...mentioning
confidence: 68%
“…Zhao et al reported that the pharmacokinetics of a murine eye might not mimic the human eye well because of the size difference. 102 Indeed, it is difficult to replicate human in vivo conditions. Thus, the results obtained from animal studies may not extend to humans.…”
Section: Key Challenges For the Futurementioning
confidence: 99%
“…Research and development are still ongoing, with controversial outcomes that make them not yet mature enough for medical use [ 46 , 47 ]. A recent publication of a nanomicelles capable of delivering Aflibercept topically to the posterior segment demonstrated choroidal neovascularization regression [ 48 ]. In current clinical use, Difluprednate (Durezol ® ), for example, is a potent steroid emulsion for topical administration.…”
Section: The Pathways and Modalities Of Drug Deliverymentioning
confidence: 99%
“…Polymers are very useful as biomaterials due to their adaptability which is unparalleled by metals and ceramics [ 69 , 70 ]. The great range of physical and chemical characteristics of polymers have made numerous applications possible such as tissue engineering and delivery vehicles for drugs/genes [ [71] , [72] , [73] , [74] , [75] ]. It is predicted that medicinal polymers alone are around 1 billion dollars in market size.…”
Section: Polymeric Biomaterials Applicationsmentioning
confidence: 99%